PELAKSANAAN PERKAWINAN ADAT MASYARAKAT DAYAK SURUK DI DESA TEKALONG KECAMATAN MENTEBAH KABUPATEN KAPUAS HULU - NIM. A1011211160, YESSICA LOLLA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Marriage under customary law is not only considered a civil agreement, but also a bond of tradition and kinship. In the Dayak Suruk community, the implementation of traditional marriage practices has undergone changes in several stages. These stages include Betonek-tonek, Bepintak tanyak, Putus jantuh, Nyu